Study The Relationship Between Learning Performance And Facilities In The Vocational Special Education Secondary School Malaysia - Omar, Roshartini; Ruslan, Nurul Athira (Journal of Technology Management and Business, 2019)
Education is very important for all individual; disabled and non-disabled; to succeed in the development of a country. The increase in the number of disabled people (OKU) registered in every year, leads to the increase number of disabled students (OKU) at government special needs school. Due respect to the condition of the students, facilities in special needs schools should be always in good condition to ensure the education and learning process occurred in smoothly. However, there is always a problem with limited number of facilities in special education schools for a number of specific areas and consists of just a few basic things; provision of ramps, defective passages and disabling toilets and so on. Beside provision of non-compliance facilities within the schools also inhibit student movement and activity. Hence, this study aims to critically examine the relationship of facilities at special school in Malaysia and learning performance. This study focus on the Vocational Special Education Secondary School within Peninsular Malaysia. To understand the idea of study in depth many information had been reviewed from previous related study areas. Based on the questionnaire of previous study proved that learning performance of disable people can be effect by facilities. An important factor to increase the learning performance of the disable people are to providing the requirement by build OKU-friendly facilities. The results of the study represent the relationship of learning performance and facilities that can be used as a guideline and awareness to Ministry of Education (Special Education Division) in order to give equalities between normal people and disabled people. Keywords: Disabled Student, Facilities, Special Education School, Learning Performance